Consensus Statement on Visual Rehabilitation in Mild Traumatic Brain Injury. Issue 6 (December 2022) - Subramanian, Prem S.; Barton, Jason J.S.; Ranalli, Paul; Smith, Craig; Francis, Courtney E.; Frishberg, Benjamin
Abstract : Optometric visual rehabilitation therapy has been used for a variety of visual disorders. Descriptively named entities such as posttrauma visual syndrome, visual midline shift syndrome, and vertical heterophoria syndrome are frequently diagnosed by neuro-optometrists and/or behavioral optometrists in patients after stroke or head injury or in the setting of dizziness and/or headache. The scientific underpinnings of these diagnoses and treatments are weak, and published clinical studies comprise case reports and case series without comparison to control populations. Neuro-ophthalmologists are frequently questioned by patients about the utility of such treatment strategies. Many ophthalmologists and neurologists also are involved in the care of patients who carry these diagnoses and undergo these visual therapies. Involved physicians may benefit from guidance about the rationale, evidence, and level of evidence for the efficacy of these therapeutic approaches.